Innovative Learning Activities for Ethnically Diverse Students in Macedonian Science Education. - Rusevska, Katerina; Barandovski, Lambe; Petruševski, M. Vladimir; Naumoska, Aleksandra; Tofilovska, Slavica; Stojanovska, Marina (Center for Educational Policy Studies Journal (CEPSj)., 2024)
A game-based approach is widely used to increase students’ motivation through their active participation, whereby research is interwoven with fun and competition is incorporated with cooperation. Working in teams or groups encourages students to exchange their opinions, to try to find solutions together or to win a game. In this way, they learn and improve skills such as collaboration and responsibility. Several activities involv-ing the 5E model as part of inquiry-based science education and an es-cape room as part of game-based learning were used in science classes (chemistry, biology and physics). The activities were designed on three different topics – gases, ecology and electrical circuits – within the project “Diversity in Science towards Social Inclusion – Non-formal Education in Science for Students’ Diversity”. The activities focused on the students’ self-concept towards science, interest in the subject, motivation and career aspirations in STEM, as well as the effectiveness of the implemented activ-ities. The study aimed to assess the potential advantages of implementing activities in an ethnically diverse environment, benefiting both students and teachers. Pre- and post-questionnaires were designed and distributed to 190 students from various primary and secondary schools in Macedo-nia. The present paper provides an overview of game-based activities as well as a brief analysis of the pre- and post-questionnaire responses from students, focusing on the topic of ecology.
Rusevska, K., Barandovski, L., Petruševski, M. V., Naumoska, A., Tofilovska, S., M. Stojanovska. (2024). Innovative Learning Activities for Ethnically Diverse Students in Macedonian Science Education. Center for Educational Policy Studies Journal (CEPSj). 14(1): 55-77. DOI: https://doi.org/10.26529/cepsj.14.1 https://cepsj.si/index.php/cepsj/issue/view/55
Keywords: game-based activities, ecology, escape room, ethnically diverse classroom, science education